Laser Engraving Machine - Shruti Mojad; Sanika Khapare; Surbhi Deshmane; Rajesh Rehpade (International Journal of Electronics Automation, 2025)
Laser engraving technology has gained significant importance across various sectors, including manufacturing and prototyping, as well as in arts, due to its high precision and adaptability. Nevertheless, the high cost of commercial laser engraving systems often renders them inaccessible to small-scale users and educational institutions. From quick prototyping and large-scale production to creative industries like arts and crafts, laser engraving technology has become a very useful tool in many different domains. The technology's capacity to produce complex designs and patterns on a range of materials with high degrees of precision, accuracy, and adaptability is largely responsible for its appeal. Despite these benefits, laser engraving devices have not yet become widely used since commercial systems are very expensive. The goal of the current project is to design and create a laser engraving machine that is economical, small, and effective in order to solve this problem. The main goal is to develop a system that keeps the key features of commercial engravers while drastically cutting costs, making the technology more affordable and useful for regular people. Because of its open-source nature, ease of programming, and widespread availability in the maker and academic communities, the Arduino UNO microcontroller is used as the main control unit. Due to these exorbitant costs, small-scale users, hobbyists, start-up companies, and educational institutions frequently cannot afford or obtain such equipment, which limits their ability to innovate and gain hands-on experience. This project aims to design and develop an affordable and compact laser engraving machine, utilizing the Arduino UNO as the primary control unit. The goal is to establish a functional, user-friendly, and customizable engraving system tailored for hobbyists, students, and small enterprises. The proposed solution incorporates open-source hardware and software, such as Arduino UNO, GRBL firmware, stepper motors, and a laser module, to execute accurate engraving operations on wood.
Keywords: Arduino uno; Engraving; G-code; InkScape; LaserGRBL